Repositioning cities through star architecture: how does it work?. Issue 2 (4th March 2018) - Alaily-Mattar, Nadia; Dreher, Johannes; Thierstein, Alain
Abstract: Public authorities' declared rationale for the commission of star architects is based on the hypothesis that due to their specific capacities, buildings designed by star architects can have significant effects on the economic and social performances of their respective cities. With a conceptual impact model on hand, this paper illustrates the specific offerings of star architectural projects and the underlying hypotheses that link these offerings to intended and effective impacts. The investigation of three case studies shows that different rationales guided the development of these 'special' projects. The application of the impact model assists in identifying these differences.